1996
DOI: 10.1161/01.cir.93.7.1439
|View full text |Cite
|
Sign up to set email alerts
|

Seeding of Vascular Grafts With Genetically Modified Endothelial Cells

Abstract: Increased TPA expression significantly decreases seeded EC adherence in vitro and in vivo. Gene therapy strategies for decreasing graft thrombosis may require expression of antithrombotic molecules that lack proteolytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Once the graft is populated, endothelial progenitor cells can provide a native endothelial cell lining in addition to secreting basement membrane and signaling molecules for the subsequent trafficking of cytoactive factors [7,71,72,73]. Overall, endothelial cells “sense” both the topography and local compliance of their extracellular microenvironment, represented primarily by the basement membrane and actively respond to changes therein [29,30,74].…”
Section: Vascular Endothelial Cellsmentioning
confidence: 99%
“…Once the graft is populated, endothelial progenitor cells can provide a native endothelial cell lining in addition to secreting basement membrane and signaling molecules for the subsequent trafficking of cytoactive factors [7,71,72,73]. Overall, endothelial cells “sense” both the topography and local compliance of their extracellular microenvironment, represented primarily by the basement membrane and actively respond to changes therein [29,30,74].…”
Section: Vascular Endothelial Cellsmentioning
confidence: 99%
“…Glial fibrillary acidic protein, a marker of astroglial cells, increases with age (68), especially in the hippocampus and entorhinal cortex, which are susceptible to neurodegeneration in AD (69 -72). Astrocytosis, the proliferation and activation of astrocytes (73), is more pronounced in AD brains than in normal brains and usually occurs in areas surrounding neuritic plaques (74,75) and neurons bearing neurofibrillary tangles (75)(76)(77)(78). Importantly, activated astrocytes in AD brains secrete many cytokines, including interleukins 1 and 6, tumor necrosis factor-␣, and acute-phase inflammatory proteins, such as ␣ 2 -macroglobulin and C-reactive protein (79 -82).…”
Section: Fig 3 Regulation Of Apoe Expression In Neuro-2a Cells By Amentioning
confidence: 99%
“…LacZ expressing endothelial cells lining the luminal surface were demonstrated 5 weeks later. Later studies showed successful retroviral transduction of endothelial cells with proangiogenic genes such tissue-plasminogen activating (TPA) factor [88]. In a similar context, saphenous vein grafts could be successfully trans-duced using an adenoviral vector [89].…”
Section: Cartilagementioning
confidence: 99%